Safety and Effectiveness of Conventional Commercial Products for Professional Tooth Bleaching: Comparative Ex Vivo Study Using AFM Microscopy and Nanoindentation - Claudio Pasquale; Nicola De Angelis; Fabrizio Barberis; Alberto Lagazzo; Elena Dellacasa; Davide Biggio; Matteo Schiaffino; Roberto Raiteri; Luca Ceseracciu; Stefano Benedicenti; Andrea Amaroli (Applied Sciences, 2023)
In modern times, patients are not only seeking oral health but also aiming for a flawless smile. Despite the progress made in aesthetic dentistry, there are instances where insufficient teeth whitening results contrast with the considerable cost of professional treatments. Patient discomfort and the potential for tooth damage further compound these challenges. In this study, we conducted a comparative split-mouth ex vivo investigation to evaluate the innovative BlancOne ULTRA+ (IDS SpA) in comparison with established professional products: Opalescence Extraboost (ULTRADENT), Zoom WhiteSpeed (Philips Research Eindhoven High Tech), and Pola Office (SDI Limited). Our initial focus was on the whitening effectiveness of each product, which was measured using a spectrophotometer. Subsequently, we assessed any structural changes in enamel post-treatment using an atomic force microscope (AFM) and a nanoindentation procedure. All tested bleaching agents demonstrated teeth-brightening effects. BlancOne ULTRA+, Zoom WhiteSpeed, and Pola Office caused minor alterations in the texture of the enamel surface within nanometric limits. However, Opalescence Extraboost exhibited notably more pronounced changes, indicating significant modifications in surface roughness and potential reductions in material hardness due to consequential shifts in mechanical properties. BlancOne ULTRA+ appears to offer the most favourable cost–benefit outcome.